MACROECONOMIC DETERMINANTS OF SEASONED EQUITY OFFERING DECISIONS IN NIGERIA - Kazeem Seun Belau; Russel Olukayode Christopher Somoye; Bamidele M. Ilo; Akinwumi Simeon Ilemobayo (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2026)
Introduction: Nigerian firms operate under volatile macroeconomic conditions that complicate their financing choices. Existing studies largely overlooked the role of broader macroeconomic forces in firms’ financing behavior by focusing on firm-specifics. This study investigated how macroeconomic conditions impact the likelihood of seasoned equity offerings (SEOs) among firms in Nigeria. Methods: This study employed panel data on 40 firms listed on the Nigerian Exchange Group between 2010 and 2025, selected using stratified random sampling. A logit regression model was used to investigate the effects of unemployment, interest rates, foreign exchange, inflation, equity value traded, gross domestic product, price-earnings ratio, and credit to the private sector on SEOs. Results: The findings reveal that inflation has a negative, while interest rates have a positive, statistically significant effect on SEO decisions. In contrast, unemployment, economic growth, and credit to the private sector exhibit marginally positive and significant relationships with SEO issuances. The study concluded that macroeconomic stability, interest rates, and financial system development are critical drivers of SEO decisions. Conclusion and suggestion: Therefore, it is recommended that policymakers prioritize inflation control, maintain balanced interest rate policies, and strengthen financial market development to enhance firms’ access to equity financing. The study also suggests that future research should incorporate behavioral factors, such as investor sentiment and media influence, to provide deeper insights into equity issuance decisions.